Pertanggung Jawaban Kepada Pelaku Pencurian yang di Lakukan Dua Orang atau Lebih dengan Bersekutu ditinjau dalam Pasal 363 Ayat (1) KE-4 KUHP (Studi Putusan Mahkamah Agung No. 1092 K/Pid/2022) - Sinaga, Sherina; Sianturi, Ronal Hasudungan; Leonardo, Frans (JURNAL LEGISIA, 2024)
The research aims to deal with thefts committed by more than two people or in collusion. The formulation of the problem is responsibility for perpetrators of theft based on Article 363 paragraph (1) of the 4th Criminal Code and the basis for inspection, the judge places criminal sanctions on theft cases based on Supreme Court Decision No. 1092 K / Pid / 2022. This type of legal research is juridically normative. The result of the discussion was criminal liability against Defendant II Moh. Asrar Abd Samad in Supreme Court decision No. 1092 K/Pid/. Aswan and his friend are believed to be legally guilty of theft.